The Complete Chloroplast Genome Sequence of Ampelopsis: Gene Organization, Comparative Analysis, and Phylogenetic Relationships to Other Angiosperms - Raman, Gurusamy; Park, SeonJoo (Frontiers in Plant Science, 2016)
Ampelopsis brevipedunculata is an economically important plant that belongs to the Vitaceae family of angiosperms. The phylogenetic placement of Vitaceae is still unresolved. Recent phylogenetic studies suggested that it should be placed in various alternative families including Caryophyllaceae, asteraceae, Saxifragaceae, Dilleniaceae, or with the rest of the rosid families. However, these analyses provided weak supportive results because they were based on only one of several genes. Accordingly, complete chloroplast genome sequences are required to resolve the phylogenetic relationships among angiosperms. Recent phylogenetic analyses based on the complete chloroplast genome sequence suggested strong support for the position of Vitaceae as the earliest diverging lineage of rosids and placed it as a sister to the remaining rosids. These studies also revealed relationships among several major lineages of angiosperms; however, they highlighted the significance of taxon sampling for obtaining accurate phylogenies. In the present study, we sequenced the complete chloroplast genome of A. brevipedunculata and used these data to assess the relationships among 32 angiosperms, including 18 taxa of rosids. The Ampelopsis chloroplast genome is 161,090 bp in length, and includes a pair of inverted repeats of 26,394 bp that are separated by small and large single copy regions of 19,036 bp and 89,266 bp, respectively. The gene content and order of Ampelopsis is identical to many other unrearranged angiosperm chloroplast genomes, including Vitis and tobacco. A phylogenetic tree constructed based on 70 protein-coding genes of 33 angiosperms showed that both Saxifragales and Vitaceae diverged from the rosid clade and formed two clades with 100% bootstrap value. The position of the Vitaceae is sister to Saxifragales, and both are the basal and earliest diverging lineages. Moreover, Saxifragales forms a sister clade to Vitaceae of rosids. Overall, the results of this study will contribute to better support of the evolution, molecular biology and genetic improvement of the plant Ampelopsis.